Environmental and economic impacts of the adoption of improved fertiliser practices in Mexico - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The GreenSeeker sensor technology has been utilized on nearly 2,000 farmer plots for fertilizer management representing more than 60,000 hectares in three regions of Mexico, leading to both economic benefits for farmers and environmental benefits in terms of avoided greenhouse gas emissions.